Connecting the dots between urban infrastructure, well-being, livability, and equity: a data-driven approach. (1st September 2022) - Das, Kirti; Ramaswami, Anu; Fan, Yingling; Cao, Jason
Abstract: Developing sustainable, livable and equitable cities is a major policy goal. However, livability metrics are amorphous, emphasizing different dimensions. This paper develops a novel data-driven approach by directly surveying subjective well-being (SWB) of urban residents, alongside satisfaction with key social–ecological–infrastructural–urban correlates to inform livability and equity priorities. Our survey is novel in quantifying SWB (Cantril ladder) of urban residents and evaluating both household- and neighborhood-level correlates while addressing confounding effects of socio-demographics and personality. We propose a three-way typology of provisioning systems—foundational, consistently important and added-bonus—based on their quantitative relationship with SWB. Implemented in the Twin-Cities USA, among 21 attributes, home heating-cooling, neighborhood greenery, access to public transportation and snow removal emerged as foundational in cold Minnesota climates; home size was consistently important and satisfaction with streets an added-bonus. Assessing inequality in foundational and consistently important categories revealed disparities by income and race, informing local infrastructure priorities for livability and equity. Key insights emerged on sufficiency and sustainability.